Non-home discharge after cardiac surgery in Australia and New Zealand: a cross-sectional study. Issue 12 (23rd December 2021) - Ramanan, Mahesh; Kumar, Aashish; Anstey, Chris; Shekar, Kiran
Abstract : Objective: To determine the proportion of patients surviving their cardiac surgery who experienced non-home discharge (NHD) over a 16-year period in Australia and New Zealand (ANZ). Design: Retrospective, multicentre, cross-sectional study over the time period 01 January 2004 to 31 December 2019. Setting: Adult patients who underwent cardiac surgery from the Australia New Zealand Intensive Care Society Adult Patient Database (APD). Participants: Adult patients (age 18 and above) who underwent index coronary artery bypass grafting, cardiac valve surgery or combined valve/coronary surgery. Exposure: The primary exposure variable was the calendar year during the which the index surgery was performed. Outcome: The primary outcome was NHD after the index surgery. NHD included discharge to locations such as nursing home, chronic care facility, rehabilitation and palliative care. Results: We analysed 252 924 index cardiac surgical admissions from 101 discrete sites with a median age of 68 years (IQR 60–76), of which 74.2% (187 662 out of 252 920) were males. Of these, 4302 (1.7%) patients died in hospital and 213 011 (84.2%) were discharged home, 18 010 (7.1%) were transferred to another hospital and 17 601 (7%) experienced NHD. In Australia, 14 457 (6.4%) of patients progressed to NHD, compared with 3144 (11.7%) in New Zealand. The rate of NHD increased significantly over time (adjusted OR per year=1.06, 95% CI, 1.06 to 1.07, p<0.001). Increasing age, female sex, non-elective surgery, surgery type and Acute Physiology and Chronic Health Evaluation III Score were all associated with significant increase in NHD. Conclusions: There was significant increase in NHD after cardiac surgery over time in ANZ. This has significant clinical relevance for informed consent discussions between healthcare providers and patients, and for healthcare services planning.